A Study Of The Value Of Mutual Cooperation Harmony In The Implementation Of Sedekah Laut Traditions During The Covid-19 Pandemic (Case Study: Implementation of the Sedekah Laut Tradition at Santolo Beach, Cikelet District, Garut Regency) - Thoriq Abdul Aziz; Ilham Muhammad Syaban (KOLABORASI: Journal of Multidisciplinary, 2024)
The implementation of sedekah laut tradition is one form of local wisdom value for the people society’s in the south coast villager of Jawa Barat, especially in Kabupaten Garut. During the Covid-19 pandemic this tradition was implemented differently than in previous years, especially with changes in systems and interaction patterns as a result of community restrictions during the Covid-19 pandemic. This study uses research methods of literature studies on several articles and publications of scientific journals with systematic literature review approach by producing research as follows 1) indicators of the value of gotong royong in the implementation of sedekah laut ceremonies undergo changes, namely the ability of cooperation, responsibility, solidarity and implementation of consensus deliberations in activities 2) social restrictions become a factor of participation in mutual assistance decreases and 3) the implementation of Sedekah Laut is carried out independently and not based on fishing areas so that funds are issued large enough 4) Changes in the value of mutual assistance is a form of change in civic disposition character of the community as an adaptive nature to emergency events one of them covid-19 pandemic.